Well‐Being, Self‐Regarding Reasons, and Morality. (15th February 2015) - Nye, Howard L. M.
<x xml:space="preserve">Abstract</x> It seems that we should want to avoid becoming intellectually disabled. It is common for philosophers to infer from this that those of us without intellectual disabilities are intrinsically better off than individuals with intellectual disabilities, and that there are consequently stronger moral reasons for others to preserve our lives than to preserve the lives of intellectually disabled individuals. In this article, I argue against this inference from what states we should prefer for ourselves to how much moral reason others have to maintain these states on our behalves. I argue that there is an important sense in which an outcome contributes to our well‐being to a certain degree, namely the extent to which others should want it out of care for us, which plays a central role in determining the moral priority of ensuring the outcome for us over ensuring distinct outcomes for others. But an outcome's contribution to our well‐being in this sense can come apart from the extent to which we should prefer it for ourselves.